Striatal Chloride Dysregulation and Impaired GABAergic Signaling Due to Cation-Chloride Cotransporter Dysfunction in Huntington’s Disease - Serranilla, Melissa; Woodin, Melanie A. (Frontiers in Cellular Neuroscience, 2022)
Intracellular chloride (Cl-) levels in mature neurons must be tightly regulated for the maintenance of fast synaptic inhibition. In the mature central nervous system (CNS), synaptic inhibition is primarily mediated by the neurotransmitter gamma-amino butyric acid (GABA), which binds to Cl- permeable GABAA receptors. The neuronal Cl- gradient is primarily maintained by the antagonistic actions of two cation-chloride cotransporters (CCCs): Cl--importing Na+-K+-Cl− co-transporter-1 (NKCC1) and Cl- -exporting K+-Cl− co-transporter-2 (KCC2). In the mature healthy brain, KCC2 expression is relatively high compared to NKCC1, leading to lower levels of intracellular Cl-, and Cl- influx upon GABAA receptor activation. In the immature brain and some diseased states, impaired KCC2 functional expression and/or enhanced expression of NKCC1 lead to intracellular Cl- accumulation and GABA-mediated excitation. In Huntington’s disease (HD), KCC2 and NKCC1 functional expression is altered, leading to GABA-mediated excitation, which contributes to the development of cognitive and motor impairments. This review summarizes the role of Cl- (dys)regulation in the healthy and HD brain, with a focus on the basal ganglia (BG) circuitry and the use of CCCs as potential therapeutic target in the treatment of HD.